Found and lost in translation: Exploring the legal protection of women from the Domestic Violence Act 2005 through the social public space of Kolkata - Mukhopadhyay, Amrita (Social and Legal Studies)
The Protection of Women from Domestic Violence Act 2005 (PWDVA) came into effect on 26 October 2006. The PWDVA introduced several legislative innovations that either are proclaimed as landmarks or remain underscored in the commentaries of the PWDVA. This article attempts to explore the landmark and the mundane PWDVA aspects by examining the implementation of the PWDVA through the relation between the formal legal sphere and the social sphere. It aims to examine how and in what ways has the formal domestic violence law fostered a legal culture engendering legal literacy of ordinary women and men. In doing so, the article explores how the implementation of the PWDVA responds to a particular sociocultural context of women experiencing violence at the hands of family members in India and offers a legal conception of domestic violence that is significantly different from the Western notion of domestic violence as interpersonal violence between two individuals. - Reproduced.
Keywords: Women; Domestic Violence Act 2005